Rancang Bangun Aplikasi Kamus Bahasa Daerah Menggunakan Flutter (Bahasa Daerah Bugis Kabupaten Pinrang) - Dillah, Nur Fadilah Rahmat; Ibrahim, Firmansyah; Rizaldy, Adhy (Journal Software, Hardware and Information Technology, 2023)
The dictionary is one of the instruments that can be used so that language differences are not an interaction obstacle. However, the Bugis Language Dictionary is only available in certain places, such as language centers, and is not widely known by the native Bugis community or outsiders. In addition to the rare number, the Bugis language dictionary is still in the form of a thick book, so it takes a relatively long time to find the desired vocabulary and is felt less effective in its use. With this, the researchers designed an application using the Flutter Framework to help people who want to learn local languages. Flutter is an open-source SDK or framework developed by Google to design or develop an application that will run on Android and iOS operating systems. The development method used is Waterfall, the testing method used to test an application is black-box, and user validation testing uses the System Usability Scale with a total of 47 respondents. This application produces an average SUS score of 74.25 with a grade scale "B" and an adjective ranking value of "Good".